Coping with Stress and Pathogenic Type A Behavior as Predictors of School Burnout - Tomaszek, Katarzyna; Muchacka-Cymerman, Agnieszka (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The purpose of the study was to evaluate the relationship between coping with stress, type A behaviourand school burnout in primary and secondary school. The study included 255 students aged between 11 to16 years (111 women and 114 men). Variables were measured by three scales: the ESSBS school-burnout,the TAB scale for type A behaviour and the How do you cope? scale and a personal questionnaire. The results indicate significant correlations between all subscales of TAB and a global level of school burnoutand the Burnout from School subscale. Inadequacy in School was not related to type A behaviour. In thelight of the obtained data, there is no relationship between school burnout and the ability to deal with stressin specific situations. The lower the level of school burnout experienced, the greater the ability to use activecoping style. A stepwise multiple regression analysis indicated that the most important predictor of school burnout is a subjective declaration about school performance. Other variables in the regression analysis are: two components of type A (time pressure and hostility), lack of active coping style and age. Those variablesexplain 42% of the variance in Global School Burnout level.